From Dakar to Amsterdam, and an ongoing practice in Burkina Faso - Ouamega-Nikiema, Micheline (Technical Centre for Agricultural and Rural Cooperation, 2019)
Solidair Switzerland took part in the experience capitalization training workshops that took place in Dakar in October 2017 and February 2018, and in Amsterdan 2019. This helped us start incorporating the capitalization approach to review our project intervention methods and monitoring strategies for improved results. After the workshops, a "champion" was identified to advocate for the institutionalization of the capitalization approach, and after several months of hard work, the process is showing results. Several developments within the organization - from the collective training of colleagues to individual interventions and support of the process by the company leaders - have been beneficial